2022
DOI: 10.1177/00048674221139962
|View full text |Cite
|
Sign up to set email alerts
|

Understanding subjective experience in psychedelic-assisted psychotherapy: The need for phenomenology

Abstract: Psychedelic-assisted psychotherapy is being investigated as a treatment for a range of psychiatric illnesses. Current research suggests that the kinds of subjective experiences induced by psychedelic compounds play key roles in producing therapeutic outcomes. To date, most knowledge of therapeutic psychedelic experiences are derived from psychometric assessments with scales such as the Mystical Experience Questionnaire. While these approaches are insightful, more nuanced and detailed descriptions of psychedeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The area of phenomenology, despite its richness of accessorial states of consciousness, remains an under-researched topic in the realm of psychedelic induced states (Houot, 2021). The qualitative element of this limited pool of information is even further from sufficient as the bulk of research utilizes quantitative means to collect data (Miceli McMillan & Fernandez, 2023). The evidence regarding the benefits of these drugs for healthy individuals has also been rather neglected as the typical population sample used in most psychedelic researches consists of individuals with a diagnosis of mental health disorder(s).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…The area of phenomenology, despite its richness of accessorial states of consciousness, remains an under-researched topic in the realm of psychedelic induced states (Houot, 2021). The qualitative element of this limited pool of information is even further from sufficient as the bulk of research utilizes quantitative means to collect data (Miceli McMillan & Fernandez, 2023). The evidence regarding the benefits of these drugs for healthy individuals has also been rather neglected as the typical population sample used in most psychedelic researches consists of individuals with a diagnosis of mental health disorder(s).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Psilocybin is a psychedelic substance that works by activating serotonin receptors. Recent research has suggested that the therapeutic effects of psychedelics cannot be attributed entirely to neurobiological causes, rather patients' subjective experience during and after psychedelics seems to play an important causal role in recovering from mental illness (McMillan & Fernandez, 2022). It has been proposed that subjective effects are necessary for enduring therapeutic effects (Yaden et al, 2022).…”
Section: The Psilocybin Experiencementioning
confidence: 99%
“…She suggests that our proposal be incorporated into a broader theoretical and methodological framework that integrates first-person and third-person data—such as neurophenomenology or non-reductive neurophilosophy (NRNP). As she argues, ‘phenomenology alone remains blind to the third-person perspective of empirical research’ (Ventura, 2023). Approaches like neurophenomenology and NRNP aim to address this shortcoming, providing ways of bridging the phenomenological focus on subjective experience with more traditional ways of investigating the mind and brain.…”
mentioning
confidence: 99%